Vpliv porodnega položaja pri iztisu ploda na poškodbo presredka - Kapus, Karmen (Obzornik zdravstvene nege, 2024)
Introduction: Effects of the birthing position on perineal trauma, which depend on local and regional midwifery/obstetric practices, such as application of manual perineal protection technique, episiotomy rates, operative delivery rates etc., have not yet been sufficiently researched. The aim of this study was to examine a potential association between birthing positions and the risk of perineal trauma in a Slovenian hospital.Methods: This retrospective cohort study included 625 women with singleton fetuses who delivered at the Jesenice General Hospital in 2021. We excluded premature deliveries, deliveries with a fetus in the pelvic or occipito-posterior insertion, vacuum extractions of the fetus, and episiotomies. Multiple logistic regression analysis was used to investigate whether the birthing position (supine (n=66), lateral (n=404), or other position (n=155)) was independently associated with perineal trauma.Results: In the majority of women included in the study (n=363, or 58%), no perineal trauma occurred. First-degree perineal tear was present in 192 women (73%), second-degree in 59 women (23%) and third- or fourth-degree in 11 women (4%). The birthing position was not significantly associated with perineal trauma (odds ratio (OR) 0.691; 95% confidence interval (CI) 0.401–1.191 for the lateral position, and OR 0.710; 95% CI 0.386–1.306 for other positions compared with the supine position).Discussion and conclusion: In a Slovenian maternity unit with a high percentage of women delivering in "flexible sacrum positions", the birthing position at delivery was not found to be an independent risk factor for perineal trauma.
Keywords: delivery; episiotomy; epiziotomija; labour; obstetric sphincter injury; perineal protection; porod; poškodbe tretje in četrte stopnje; varovanje presredka